PENGEMBANGAN METODE STRESSED SHEETING WELD PADA PENGELASAN PLAT BERPENGUAT DENGAN VARIASI TEMPERATUR PREHEAT - Yustiasih Purwaningrum; Triyono Triyono; Kelvin Koharto; Adit Suhartanto (Teknoin, 2014)
This research investigates  stressed sheeting welded (SSW) effects of stiffened thin plate structure with preheat temperature  variations. Stiffened thin plate structure is a structure that  consists of frame and sheet that used on  vehicle structure because of requirement low volume materials. The principle of  SSW is installation of sheeting on the frame is done by pulling the sheeting in hot conditions so the sheeting after joined with the frame has the flat surface. Lap joints of  SS 400 with thickness of  1 mm dan 3 mm were made using Gas Metal Arc Welding. The preheat temperature that used were 50°C, 60°C and 70°C. The mechanical properties were measured with respect to strength and hardness while physical properties were examined based on the distortion, micro and macrostructure. Results show that the distortion of weld metal with preheat temperatures 50°C, 60°C and 70°C are 1.02; 2.06; and 2.22 mm respectively. This values is better than weld metal without  SSW that has distortion 3.02 mm. The tensile  strength of weld metals with SSW method  is 20% higher than the weld metal  without SSW. Ferrite and pearlite structure appeared in based metal and HAZ region while weld metal had acicular ferrite and grain boundary ferrite structure.